Semiotics Unbounded : Interpretive Routes through the Open Network of Signs - Petrilli, Susan (Book collections on Project MUSE., 2005)
Semiotics Unbounded offers a new and original survey of the science of signs, evaluating it in relation to the problems of our time, not only of a scientific order, but also the problems concerning everyday social life.